Pola Pertumbuhan Jamur Candida spp. pada urin Penderita Diabetes Melitus dengan Glukosa Terkontrol dan Tidak Terkontrol: Penelitian Laboratorium - Anwar, Aan Yulianingsih; Jakaria, Febrianti (Health Information : Jurnal Penelitian, 2023)
Diabetes mellitus is a chronic metabolic disorder caused by the pancreas not producing enough insulin or the body being unable to use the insulin produced effectively. DM sufferers who have uncontrolled glucose suffer from abnormalities in the function of the main defense cells. DM sufferers experience disruption of these main defense cells due to an imbalance in the functions of chemotaxis and phagocytosis which makes diabetes mellitus sufferers more susceptible to infection. High blood sugar levels also damage the system, thereby reducing the sufferer's sensitivity to Candida albicans fungal infections. The genital area in diabetes mellitus patients contains a lot of glucose which is a nutrient for fungal growth. The aim of this research was to examine the growth patterns of Candida spp. In the urine of DM sufferers, glucose is controlled and uncontrolled. The method used is descriptive analysis with a cross sectional design. The results of the study showed that of the 30 respondents with controlled glucose, 1 was found to be positive for Candida spp. Meanwhile, 11 of the 30 respondents with uncontrolled glucose were found to be positive for Candida spp. In his urine. The conclusion of the research is that there is a relationship between the growth of Candida spp. In controlled and uncontrolled glucose with p value (0.001<0.05).